A Literature Review on the Application of Technology During Covid-19 and Its Relationship to Performance - Kraugusteeliana Kraugusteeliana; Endang Surjati; Abu Muna Almaududi Ausat; Susatyo Adhi Pramono; Hamonangan Kinantan Prabu (Universitas Dharma Wacana, 2022)
This is not the only reason why the Covid-19 epidemic has damaged numerous people. Individuals and institutions must be able to adapt to changing circumstances. Individually and organizationally, one of them is to adapt more to technology advances in order to improve the long-term sustainability of performance. Using a descriptive qualitative technique, the author of this study will describe the use of technology during the Covid-19 pandemic and how it connects to performance. The outcomes of this study indicate that technology is a wonderful instrument for overcoming adversity and becoming a solution for surviving and competing in the age of disruption, especially during a crisis. During the covid-19 pandemic, it is crucial for the government to continue providing support such as financing, education and training, mentoring from experts, technical advice, and other forms of assistance to businesses that lack the necessary resources in order for them to highlight the advantages of expanding the use of digital technology in Indonesia. On the other hand, businesses are not required to rely solely on the government; rather, they should endeavor to eliminate any technological impediments they may face by maximizing the government's assistance, initiatives, and incentives. As intelligent persons and organizations, we must be flexible in order to improvise with technological complexity. Because one of the fundamental purposes of technology is to contribute to economic growth. The weakness of the study is that it does not yet focus on a specific unit of analysis, namely the type of technology in question. As a result, it is suggested that future research concentrate on the sort of technology mentioned, utilizing a quantitative approach method on specific objects with a high number of samples, and supplementing data gathering approaches with interviews. This paper can also be used as a supplement to other sources highlighting the significance of technology during the Covid-19 pandemic